Tetratricopeptide repeat domain 7A is a nuclear factor that modulates transcription and chromatin structure. Issue 1 (December 2018) - El-Daher, Marie-Therese; Cagnard, Nicolas; Gil, Marine; Cruz, Marie; Leveau, Claire; Sepulveda, Fernando; Zarhrate, Mohammed; Tores, Frédéric; Legoix, Patricia; Baulande, Sylvain; Villartay, Jean; Almouzni, Geneviève; et al.
Abstract A loss-of-function mutation in tetratricopeptide repeat domain 7A (TTC7A) is a recently identified cause of human intestinal and immune disorders. However, clues to related underlying molecular dysfunctions remain elusive. It is now shown based on the study of TTC7A-deficient and wild-type cells that TTC7A is an essential nuclear protein. It binds to chromatin, preferentially at actively transcribed regions. Its depletion results in broad range of epigenomic changes at proximal and distal transcriptional regulatory elements and in altered control of the transcriptional program. Loss of WT_TTC7A induces general decrease in chromatin compaction, unbalanced cellular distribution of histones, higher nucleosome accessibility to nuclease digestion along with genome instability, and reduced cell viability. Our observations characterize for the first time unreported functions for TTC7A in the nucleus that exert a critical role in chromatin organization and gene regulation to safeguard healthy immune and intestinal status.